Conflict Resolution Through Participatory Rangeland Management: A Case Study from Osobey-Globo Rangeland Unit, Filtu Woreda, Somali Region, Ethiopia - Abdullahi, Mohammed Said (CGIAR System Organization, 2024)
In Osobey-Golbo, Ethiopia, HEAL and PRM supported the creation of a rangeland management institute, a rangeland council for the entire unit and smaller rangeland committees at the sub-unit level. The impact observed in the Osobey-Golbo rangeland unit has been significant, leading to a notable decrease in conflicts stemming from land grabbing. Community members have recognized that private grazing land is a major cause of contention. As part of the new plans, it was agreed to remove barriers dividing private land and introduce a bylaw imposing fines or potential imprisonment for those who erect such barriers.